2002
DOI: 10.1089/107555302760253676
|View full text |Cite
|
Sign up to set email alerts
|

Types of Alternative Medicine Used by Patients with Breast, Colon, or Prostate Cancer: Predictors, Motives, and Costs

Abstract: Given the high prevalence of use and that patients believed that alternative medicine improved their well-being, clinicians should show an open mind toward these treatment choices and encourage frank discussion. Familiarity and some knowledge regarding use of alternative medicine is important in cases where interactions between conventional and alternative medicine may occur. It is also important to identify potential patient needs for mental health support beyond conventional care and support patients who wan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
150
7

Year Published

2006
2006
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(170 citation statements)
references
References 15 publications
13
150
7
Order By: Relevance
“…The use of alternative medicine and the treatment delay caused by that has been well-documented in the past [9,22,23]. In the developed countries, the use of alternative medicine is primarily attributable to the psychological distress over potential, often mutilating treatments [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…The use of alternative medicine and the treatment delay caused by that has been well-documented in the past [9,22,23]. In the developed countries, the use of alternative medicine is primarily attributable to the psychological distress over potential, often mutilating treatments [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed to be higher in breast and prostate cancer populations than in populations with other cancer diagnoses 20,23 . The heightened interest in CAM in these populations may be a consequence of the proactive nature of these patient groups with regard to advocacy and self-care (that is, support-group membership).…”
Section: 11mentioning
confidence: 99%
“…22,24,28,29,34,36,37,39,40,50,51,54,56,[58][59][60]62 The remaining studies collected data from broader study populations and reported the prevalence of CAM use for subgroups including men with prostate cancer. 23,[25][26][27][30][31][32][33]35,38,[41][42][43][44][45][46][47][48][49]52,53,55,57,61,63 The characteristics of all 42 included studies are summarised in Table 2 …”
Section: Study Selection and Characteristicsmentioning
confidence: 99%